Young-Old City-Dwellers Outperform Village Counterparts in Attention and Verbal Control Tasks - Stepankova Georgi, Hana; Frydrychova, Zuzana; Horakova Vlckova, Karolina; Vidovicova, Lucie; Sulc, Zdenek; Lukavsky, Jiri (Frontiers in Psychology, 2019)
Cognitive performance is dynamic and shaped by individual biological and environmental factors throughout life. In psychology, besides the effects of age, education, and other often studied factors, the complexity of the lived-in environment and urbanicity in that context are yet to be elucidated. In this observational cross-sectional study, we compare cognitive performance in standard neuropsychological tests in healthy older persons from three different types of settlements in the Czech Republic: the capital city of Prague, towns, and villages. The groups were equal in terms of the age-band (60-74 years), the distribution of gender, education, past and current leisure activities, and cognitive health status (MMSE score). The results showed that Prague citizens had consistently better performance in all verbal tests (for memory and verbal control, i.e., executive function) and attention than persons from other areas. The groups did not differ in timed visuo-graphomotor performance. The conclusion is that the complex environment of a city may promote, in the long-term, certain cognitive abilities, distinguishable even in a developed, culturally homogenous country. The implications are: (a) the description of samples used in normative studies should include information on the lived-in environment for the reference of researchers and clinicians; and (b) individual clinical assessment should reflect the role of the patient’s environment where appropriate. The exact mechanisms and causes of the differences need further investigation.